Photocatalytic polyether-ether-ketone ion exchange membrane as well as preparation method and application thereof
By grafting Bi@CoTiO3 photocatalyst on polyether ether ketone material, a reusable photocatalytic polyether ether ketone ion exchange membrane was prepared, which solved the problem of difficulty in photocatalyst recovery and achieved efficient antibiotic degradation and heavy metals Restore and avoid secondary pollution and resource waste.
Patent Information
- Application Number
- CN202510018124.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The recycling of existing photocatalysts is difficult, resulting in secondary pollution and waste of resources.
Polyether ether ketone material is used as the reaction film matrix, and thin films with amino and carboxyl pendant are prepared by casting film method and electrospinning method, and Bi@CoTiO3 photocatalyst is branched onto the film to form a reusable Photocatalytic polyether etherketone ion exchange membrane.
The efficient degradation of antibiotics and the efficient reduction of heavy metal ions are achieved, and the separation of photocatalysts and reaction media makes them reusable, avoiding secondary pollution and waste of resources.
Smart Images

Figure CN119425421A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer chemistry, and in particular relates to a photocatalytic polyetheretherketone ion exchange membrane and a preparation method and application thereof. Background Art
[0002] With the development of science and the progress of the times, people are developing industry rapidly. At the same time, the improper discharge of industrial wastewater and the research and development and production of chemical agents have led to the deposition of a large number of heavy metals (mercury, chromium, lead) and antibiotics (tetracycline (TC), amoxicillin (AM), carbamazepine (CBZ), ciprofloxacin (CIP), norfloxacin (NOR), etc.) into water resources, aggravating water pollution. Domestic water, such as daily washing, cooking, and sanitary water, flows into the sewer with detergents, organic matter, nitrogen and phosphorus, which accumulate into a large amount, causing lakes and streams to become eutrophic, algae to grow wildly, and water bodies to become hypoxic. Excessive pesticides and fertilizers are washed into the ground and into ditches with rainwater, destroying the soil and water ecology, causing the water environment to become more complex and harsh. People in modern society are facing the threat of serious water pollution.
[0003] Photocatalytic technology has the characteristics of high efficiency, environmental friendliness and sustainable development in water pollution control, and has attracted widespread attention. However, most traditional photocatalysts are in powder or granular form, which are difficult to recycle and easily cause secondary pollution. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of difficulty in recovering photocatalysts in the prior art. The present invention provides a photocatalytic polyetheretherketone ion exchange membrane and a preparation method and application thereof.
[0005] The technical solution of the present invention is as follows: One of the purposes of the present invention is to provide a method for preparing a photocatalytic polyetheretherketone ion exchange membrane, the method comprising: S1: drying polyetheretherketone powder, mixing it with an antioxidant and a silane coupling agent, extruding it using a twin-screw extruder, cooling it, and pelletizing it to obtain polyetheretherketone pellets; S2: putting the polyetheretherketone pellets obtained in S1 into a single screw extruder, extruding and casting, and longitudinally stretching to obtain a polyetheretherketone film; S3: mixing the polyetheretherketone film obtained in S2 with sodium borohydride and pouring into a dimethyl sulfoxide solution, performing ultrasonic dispersion, and after the reaction is complete, washing and drying to obtain a polyetheretherketone film with hydroxyl groups on the surface; S4: immersing the polyetheretherketone film with hydroxyl groups on the surface obtained in S3 in an acetic acid solution of 4-aminobenzoic acid, and after the reaction is complete, washing and drying to obtain a polyetheretherketone film containing amino and carboxyl side groups; S5: mixing cobalt acetate tetrahydrate, tetrabutyl titanate, ethanol, N'N-dimethylformamide and acetic acid solution, and then adding polyvinyl pyrrolidone to complete the reaction to obtain cobalt titanate spinning gel; S6: The spinning gel obtained in S5 is loaded into a syringe with a stainless steel needle, and fibers are prepared by electrospinning, and the fibers are calcined at high temperature to obtain CoTiO3 nanofibers; S7: mixing the CoTiO3 nanofibers obtained in S6 with bismuth nitrate and ethylene glycol, and transferring the mixture into a photocatalytic reactor, and obtaining Bi@CoTiO3 after the reaction is complete; S8: Mix the polyetheretherketone film containing amino and carboxyl side groups obtained in S4, the Bi@CoTiO3 obtained in S7 and the silane coupling agent aqueous solution, and heat them for reaction to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0006] It is further defined that the antioxidant in S1 is 3-5% of the mass of the polyetheretherketone powder, the silane coupling agent is 3-5% of the mass of the polyetheretherketone powder, and the extrusion temperature is 370-390°C; the extrusion temperature in S2 is 350-370°C, and the thickness of the polyetheretherketone film is 0.15-0.5 mm.
[0007] It is further defined that the mass ratio of polyetheretherketone film and sodium borohydride in S3 is 1.5~3:1, the ultrasonic dispersion is 1~2h, the reaction temperature is 100~160°C, and the reaction time is 12~24h.
[0008] It is further defined that the concentration of 4-aminobenzoic acid in S4 is 0.2-0.5 g / mL, and the reaction time is 4-8 h.
[0009] It is further defined that in S5, the ratio of cobalt acetate tetrahydrate, tetrabutyl titanate, ethanol, N'N-dimethylformamide and acetic acid is 15-50 g:20-70 mL:160 mL:20 mL:20 mL, and the ratio of cobalt acetate tetrahydrate and polyvinyl pyrrolidone is 15-50 g:15-50 g.
[0010] It is further defined that the parameters of the electrospinning method in S6 are: the distance between the needle and the tin foil is 15-20 cm, the spinning voltage is 15-20 kV, and the spinning speed is 0.3-0.6 mL / h.
[0011] It is further defined that the calcination temperature in S6 is 550-700°C, the heating rate is 2°C / min, and the calcination time is 2-6h.
[0012] It is further defined that the ratio of CoTiO3 nanofibers, bismuth nitrate and ethylene glycol in S7 is 10g:0.38~0.76g:100mL; the concentration of the silane coupling agent aqueous solution in S8 is 3wt%, and the ratio of the polyetheretherketone film containing amino and carboxyl side groups, Bi@CoTiO3 and the silane coupling agent aqueous solution is 100g:10~30g:250mL.
[0013] The second object of the present invention is to provide a photocatalytic polyetheretherketone ion exchange membrane, which is prepared by the above-mentioned preparation method.
[0014] The third object of the present invention is to provide an application of the above-mentioned photocatalytic polyetheretherketone ion exchange membrane in treating water pollution.
[0015] Compared with the prior art, the specific advantages of the present invention are as follows: (1) The photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention uses a polyetheretherketone material with excellent chemical corrosion resistance, UV light degradation resistance and stability as a reaction membrane matrix, composites a photocatalyst on the polyetheretherketone film, and uses the principle of photocatalysis to prepare an ion exchange membrane with the ability to degrade antibiotics and reduce heavy metal ions. The photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention can adapt to various harsh and complex pollution environments, and can also separate the photocatalyst from the reaction medium for repeated use, which can save resources and avoid secondary waste.
[0016] (2) The photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention is prepared by using a cast film method to prepare a polyetheretherketone film with amino and carboxyl side groups, and by using an electrospinning method to prepare a perovskite compound CoTiO3 nanofiber. By using the ion conjugation effect of non-precious metals, non-precious metal Bi is deposited on the CoTiO3 nanofiber by a photodeposition method to prepare Bi@CoTiO3. Finally, Bi@CoTiO3 is grafted onto the polyetheretherketone film by a chemical grafting method to prepare a photocatalytic polyetheretherketone film. Depositing Bi on CoTiO3 nanofibers can enhance the photocatalytic response of CoTiO3. Co in Bi@CoTiO3 2+ 、Ti 4+ Metal ions can form stable coordination bonds with carboxyl groups, so Bi@CoTiO3 can be tightly combined with the polyetheretherketone film, and its performance remains unchanged during repeated use.
[0017] (3) The photocatalytic polyetheretherketone film prepared by the present invention has good degradation properties for antibiotics and high reduction rate for heavy metal ions. The degradation rates of the antibiotics amoxicillin, carbamazepine and norfloxacin prepared by the photocatalytic polyetheretherketone film within 1 hour are 93.54%, 88.22% and 83.42%, respectively. The reduction rate of the heavy metal ion Cr(VI) prepared by the photocatalytic polyetheretherketone film within 10 minutes is 99.35%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The degradation diagram of amoxicillin, carbamazepine and norfloxacin by the photocatalytic polyetheretherketone film prepared in Example 1; Figure 2 This is a graph showing the reduction of heavy metal ions Cr(VI) by the photocatalytic polyetheretherketone film prepared in Example 1; Figure 3 The photocatalytic polyetheretherketone film prepared in Example 1 and Comparative Examples 1-3 degrades amoxicillin; Figure 4 The photocatalytic polyetheretherketone film prepared in Example 1 and Comparative Examples 1-3 degrades carbamazepine; Figure 5 The photocatalytic polyetheretherketone film prepared in Example 1 repeatedly degrades amoxicillin; Figure 6 This is a picture of the photocatalytic polyetheretherketone film prepared in Example 1. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0021] Embodiment 1: 100g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 160°C for 4h, then poured into a mixer with 3g of antioxidant 1024 and 5g of silane coupling agent N-2-aminoethyl-3-aminopropyltrimethoxysilane, mixed for 30min, placed in a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain polyetheretherketone pellets. The polyetheretherketone pellets were placed in a single-screw extruder, extruded through a T-die at 370°C, and stretched longitudinally to obtain a polyetheretherketone film with a thickness of 0.15mm; 100 g of the obtained polyetheretherketone film and 50 g of sodium borohydride were poured into 500 mL of dimethyl sulfoxide solution for ultrasonic dispersion for 2 h, reacted at 120° C. for 16 h, cooled to room temperature, washed the solid precipitate with ethanol, 10% hydrochloric acid aqueous solution and deionized water in turn, and then vacuum dried to obtain a polyetheretherketone film with hydroxyl groups on the surface; 100 g of the hydroxyl-containing polyetheretherketone film was immersed in 500 mL of 0.3 g / mL 4-aminobenzoic acid acetic acid solution, stirred at room temperature for 8 h, and then washed with acetic acid, deionized water and acetone in turn, and vacuum dried to obtain a polyetheretherketone film containing amino and carboxyl side groups; 32.182 g of cobalt acetate tetrahydrate and 25 mL of tetrabutyl titanate were poured into a mixed solution of 160 mL of ethanol, 20 mL of N'N-dimethylformamide and 20 mL of acetic acid, and stirred for 4 h. Then, 32 g of polyvinyl pyrrolidone was slowly added to the suspension at a rate of 2 g / min and stirred for 8 h to obtain cobalt titanate fiber gel. The fiber gel was loaded into a 100 mL syringe with a stainless steel needle, and the syringe was placed on an electrospinning machine with the needle at a distance of 15 cm from the tin foil, the spinning voltage was 20 kV, the spinning speed was 0.5 mL / h, and electrospinning was performed to collect the spun fibers; The spun fibers were transferred into a crucible, placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, and calcined at a constant temperature for 4 hours. After natural cooling, the fibers were washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours to obtain CoTiO3 nanofibers. 20g CoTiO3 nanofibers and 1.134g bismuth nitrate were placed in 100mL ethylene glycol solution, ultrasonically dispersed for 20min, transferred to a photocatalytic reactor, and reacted for 8h under the irradiation of a 300W xenon lamp equipped with a cutoff filter (λ≥420nm), and washed with deionized water and anhydrous ethanol to obtain Bi@CoTiO3; Pour 100g of polyetheretherketone film containing amino and carboxyl side groups and 20g of Bi@CoTiO3 into 250mL of 3% by mass N-2-aminoethyl-3-aminopropyltrimethoxysilane aqueous solution, stir, hydrolyze at 70°C for 8h, wash and dry to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0022] Embodiment 2: 100g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 160°C for 4h, then poured into a mixer with 3g of antioxidant 1024 and 5g of silane coupling agent N-2-aminoethyl-3-aminopropyltrimethoxysilane, mixed for 30min, placed in a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain polyetheretherketone pellets. The polyetheretherketone pellets were placed in a single-screw extruder, extruded through a T-die at 370°C, and stretched longitudinally to obtain a polyetheretherketone film with a thickness of 0.15mm; 100 g of the obtained polyetheretherketone film and 50 g of sodium borohydride were poured into 500 mL of dimethyl sulfoxide solution for ultrasonic dispersion for 2 h, reacted at 120° C. for 16 h, cooled to room temperature, washed the solid precipitate with ethanol, 10% hydrochloric acid aqueous solution and deionized water in turn, and then vacuum dried to obtain a polyetheretherketone film with hydroxyl groups on the surface; 100 g of the hydroxyl-containing polyetheretherketone film was immersed in 500 mL of 0.3 g / mL 4-aminobenzoic acid acetic acid solution, stirred at room temperature for 8 h, and then washed with acetic acid, deionized water and acetone in turn, and vacuum dried to obtain a polyetheretherketone film containing amino and carboxyl side groups; Pour 16.092 g of cobalt acetate tetrahydrate and 12.5 mL of tetrabutyl titanate into a mixed solution of 80 mL of ethanol, 10 mL of N'N-dimethylformamide and 10 mL of acetic acid, stir for 4 h, then slowly add 16 g of polyvinyl pyrrolidone to the suspension at a rate of 2 g / min, stir for 8 h, and obtain cobalt titanate fiber gel. Load the fiber gel into a 100 mL syringe with a stainless steel needle, place the syringe on an electrospinning machine, with the needle at a distance of 15 cm from the tin foil, the spinning voltage at 20 kV, the spinning speed at 0.5 mL / h, perform electrospinning, and collect the spun fibers; The spun fibers were transferred into a crucible, placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, and calcined at a constant temperature for 4 hours. After natural cooling, the fibers were washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours to obtain CoTiO3 nanofibers. 10g CoTiO3 nanofibers and 0.567g bismuth nitrate were placed in 100mL ethylene glycol solution, ultrasonically dispersed for 20min, transferred to a photocatalytic reactor, and reacted for 8h under the irradiation of a 300W xenon lamp equipped with a cutoff filter (λ≥420nm), and washed with deionized water and anhydrous ethanol to obtain Bi@CoTiO3; Pour 100g of polyetheretherketone film containing amino and carboxyl side groups and 20g of Bi@CoTiO3 into 250mL of 3% mass fraction N-2-aminoethyl-3-aminopropyltrimethoxysilane solution, stir, hydrolyze at 70°C for 8h, wash and dry to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0023] Embodiment 3: 100g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 160°C for 4h, then poured into a mixer with 3g of antioxidant 1024 and 5g of silane coupling agent N-2-aminoethyl-3-aminopropyltrimethoxysilane, mixed for 30min, placed in a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain polyetheretherketone pellets. The polyetheretherketone pellets were placed in a single-screw extruder, extruded through a T-die at 370°C, and stretched longitudinally to obtain a polyetheretherketone film with a thickness of 0.15mm; 100 g of the obtained polyetheretherketone film and 50 g of sodium borohydride were poured into 500 mL of dimethyl sulfoxide solution for ultrasonic dispersion for 2 h, reacted at 120° C. for 16 h, cooled to room temperature, washed the solid precipitate with ethanol, 10% hydrochloric acid aqueous solution and deionized water in turn, and then vacuum dried to obtain a polyetheretherketone film with hydroxyl groups on the surface; 100 g of the hydroxyl-containing polyetheretherketone film was immersed in 500 mL of 0.3 g / mL 4-aminobenzoic acid acetic acid solution, stirred at room temperature for 8 h, and then washed with acetic acid, deionized water and acetone in turn, and vacuum dried to obtain a polyetheretherketone film containing amino and carboxyl side groups; Pour 48.276 g of cobalt acetate tetrahydrate and 38 mL of tetrabutyl titanate into a mixed solution of 160 mL of ethanol, 20 mL of N'N-dimethylformamide and 20 mL of acetic acid, stir for 4 h, then slowly add 48 g of polyvinyl pyrrolidone to the suspension at a rate of 2 g / min, stir for 8 h, and obtain cobalt titanate fiber gel. Load the fiber gel into a 100 mL syringe with a stainless steel needle, place the syringe on an electrospinning machine, with the needle at a distance of 15 cm from the tin foil, the spinning voltage at 20 kV, the spinning speed at 0.5 mL / h, perform electrospinning, and collect the spun fibers; The spun fibers were transferred into a crucible, placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, and calcined at a constant temperature for 4 hours. After natural cooling, the fibers were washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours to obtain CoTiO3 nanofibers. 30g CoTiO3 nanofibers and 1.7g bismuth nitrate were placed in 100mL ethylene glycol solution, ultrasonically dispersed for 20min, transferred to a photocatalytic reactor, and reacted for 8h under the irradiation of a 300W xenon lamp equipped with a cutoff filter (λ≥420nm), and washed with deionized water and anhydrous ethanol to obtain Bi@CoTiO3; Pour 100g of polyetheretherketone film containing amino and carboxyl side groups and 20g of Bi@CoTiO3 into 250mL of 3% by mass N-2-aminoethyl-3-aminopropyltrimethoxysilane aqueous solution, stir, hydrolyze at 70°C for 8h, wash and dry to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0024] Comparative Example 1: 100g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 160°C for 4h, then poured into a mixer with 3g of antioxidant 1024 and 5g of silane coupling agent N-2-aminoethyl-3-aminopropyltrimethoxysilane, mixed for 30min, placed in a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain polyetheretherketone pellets. The polyetheretherketone pellets were placed in a single-screw extruder, extruded through a T-die at 370°C, and stretched longitudinally to obtain a polyetheretherketone film with a thickness of 0.15mm; 100 g of the obtained polyetheretherketone film and 50 g of sodium borohydride were poured into 500 mL of dimethyl sulfoxide solution for ultrasonic dispersion for 2 h, reacted at 120° C. for 16 h, cooled to room temperature, washed the solid precipitate with ethanol, 10% hydrochloric acid aqueous solution and deionized water in turn, and then vacuum dried to obtain a polyetheretherketone film with hydroxyl groups on the surface; 100 g of the hydroxyl-containing polyetheretherketone film was immersed in 500 mL of 0.3 g / mL 4-aminobenzoic acid acetic acid solution, stirred at room temperature for 8 h, and then washed with acetic acid, deionized water and acetone in turn, and vacuum dried to obtain a polyetheretherketone film containing amino and carboxyl side groups; 32.182 g of cobalt acetate tetrahydrate and 25 mL of tetrabutyl titanate were poured into a mixed solution of 160 mL of ethanol, 20 mL of N'N-dimethylformamide and 20 mL of acetic acid, and stirred for 4 h. Then, 32 g of polyvinyl pyrrolidone was slowly added to the suspension at a rate of 2 g / min and stirred for 8 h to obtain cobalt titanate fiber gel. The fiber gel was loaded into a 100 mL syringe with a stainless steel needle, and the syringe was placed on an electrospinning machine with the needle at a distance of 15 cm from the tin foil, the spinning voltage was 20 kV, the spinning speed was 0.5 mL / h, and electrospinning was performed to collect the spun fibers; The spun fibers were transferred into a crucible, placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, and calcined at a constant temperature for 4 hours. After natural cooling, the fibers were washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours to obtain CoTiO3 nanofibers. Pour 100g of polyetheretherketone film containing amino and carboxyl side groups and 20g of CoTiO3 into 250mL of 3% by mass N-2-aminoethyl-3-aminopropyltrimethoxysilane aqueous solution, stir, hydrolyze at 70°C for 8h, wash and dry to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0025] Comparative Example 2: 100g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 160°C for 4h, then poured into a mixer with 3g of antioxidant 1024 and 5g of silane coupling agent N-2-aminoethyl-3-aminopropyltrimethoxysilane, mixed for 30min, placed in a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain polyetheretherketone pellets. The polyetheretherketone pellets were placed in a single-screw extruder, extruded through a T-die at 370°C, and stretched longitudinally to obtain a polyetheretherketone film with a thickness of 0.15mm; 100 g of the obtained polyetheretherketone film and 50 g of sodium borohydride were poured into 500 mL of dimethyl sulfoxide solution for ultrasonic dispersion for 2 h, reacted at 120° C. for 16 h, cooled to room temperature, washed the solid precipitate with ethanol, 10% hydrochloric acid aqueous solution and deionized water in turn, and then vacuum dried to obtain a polyetheretherketone film with hydroxyl groups on the surface; 100 g of the hydroxyl-containing polyetheretherketone film was immersed in 500 mL of 0.3 g / mL 4-aminobenzoic acid acetic acid solution, stirred at room temperature for 8 h, and then washed with acetic acid, deionized water and acetone in turn, and vacuum dried to obtain a polyetheretherketone film containing amino and carboxyl side groups; 32.182 g of cobalt acetate tetrahydrate and 25 mL of tetrabutyl titanate were poured into a mixed solution of 160 mL of ethanol, 20 mL of N'N-dimethylformamide and 20 mL of acetic acid, and stirred for 4 h. Then, 32 g of polyvinyl pyrrolidone was slowly added to the suspension at a rate of 2 g / min and stirred for 8 h to obtain cobalt titanate fiber gel. The fiber gel was loaded into a 100 mL syringe with a stainless steel needle, and the syringe was placed on an electrospinning machine with the needle at a distance of 15 cm from the tin foil, the spinning voltage was 20 kV, the spinning speed was 0.5 mL / h, and electrospinning was performed to collect the spun fibers; The spun fibers were transferred into a crucible, placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, and calcined at a constant temperature for 4 hours. After natural cooling, the fibers were washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours to obtain CoTiO3 nanofibers. 20g CoTiO3 nanofibers and 0.378g bismuth nitrate were placed in 100mL ethylene glycol solution, ultrasonically dispersed for 20min, transferred to a photocatalytic reactor, and reacted for 8h under the irradiation of a 300W xenon lamp equipped with a cutoff filter (λ≥420nm), and washed with deionized water and anhydrous ethanol to obtain Bi@CoTiO3; Pour 100g of polyetheretherketone film containing amino and carboxyl side groups and 20g of Bi@CoTiO3 into 250mL of 3% by mass N-2-aminoethyl-3-aminopropyltrimethoxysilane aqueous solution, stir, hydrolyze at 70°C for 8h, wash and dry to obtain a photocatalytic polyetheretherketone ion exchange membrane.
[0026] Comparative Example 3: The preparation steps are different from those of Comparative Example 2 in that the amount of bismuth nitrate used is 1.89 g, and the remaining steps are the same as those of Comparative Example 2.
[0027] Degradation of antibiotics test: 20 mg of the photocatalytic polyetheretherketone ion exchange membrane prepared in Example 1 was added to 20 mL of 40 ppm aqueous solutions of amoxicillin, carbamazepine and norfloxacin, stirred in the dark for 20 min to allow the adsorption-desorption equilibrium between the antibiotics and the surface of the ion membrane, and then placed under visible light (λ>420 nm) for continued testing. During the test, 2 mL of the suspension was taken out every 10 min, centrifuged, and the pollutant concentration was measured at the maximum absorption wavelength of 254, 285, and 278 nm using an ultraviolet spectrophotometer, and the adsorption rate was calculated, which was C / C0 (C=maximum absorbance of reaction-minimum absorbance of reaction; C0=initial maximum absorbance-initial minimum absorbance).
[0028] Heavy metal ion reduction test: 20 mg of the photocatalytic polyetheretherketone ion exchange membrane prepared in Example 1 was added to a mixed solution of 20 mL of K2Cr2O7 (160 ppm) aqueous solution and 20 mL of isopropanol, and stirred in the dark for 20 min to allow the adsorption-desorption equilibrium between K2Cr2O7 and the surface of the ion membrane, and then placed under visible light (λ>420 nm) for continued testing. During the test, 2 mL of the suspension was taken out every 2 min, centrifuged, and the pollutant concentration was measured at the maximum absorption wavelength of 365 nm using an ultraviolet spectrophotometer to calculate the heavy metal ion reduction rate, reduction rate = C / C0 (C = maximum absorbance of the reaction - minimum absorbance of the reaction; C0 = initial maximum absorbance - initial minimum absorbance).
[0029] Degradation of Amoxicillin Test: 20 mg of the photocatalytic polyetheretherketone ion exchange membrane prepared in Example 1 and Comparative Examples 1-3 were added to 20 mL of amoxicillin aqueous solution with a concentration of 40 ppm, stirred in the dark for 20 min to allow the adsorption-desorption equilibrium of amoxicillin and the surface of the ion membrane, and then placed under visible light (λ>420 nm) for continued testing. During the test, 2 mL of the suspension was taken out every 10 min, centrifuged, and the pollutant concentration was measured at the maximum absorption wavelength of 254, 285, and 278 nm using an ultraviolet spectrophotometer, and the adsorption rate was calculated, adsorption rate = C / C0 (C = maximum absorbance of reaction - minimum absorbance of reaction; C0 = initial maximum absorbance - initial minimum absorbance).
[0030] Degradation of Carbamazepine Test: 20 mg of the photocatalytic polyetheretherketone ion exchange membrane prepared in Example 1 and Comparative Examples 1-3 were added to 20 mL of a 40 ppm carbamazepine aqueous solution, stirred in the dark for 20 min to allow the adsorption-desorption equilibrium of carbamazepine on the surface of the ion membrane, and then placed under visible light (λ>420 nm) for continued testing. During the test, 2 mL of the suspension was taken out every 10 min, centrifuged, and the pollutant concentration was measured at the maximum absorption wavelength of 254, 285, and 278 nm using an ultraviolet spectrophotometer, and the adsorption rate was calculated, adsorption rate = C / C0 (C = maximum absorbance of the reaction - minimum absorbance of the reaction; C0 = initial maximum absorbance - initial minimum absorbance).
[0031] Photocatalytic PEEK ion exchange repeatability test: 20 mg of the photocatalytic polyetheretherketone ion exchange membrane prepared in Example 1 was added to 20 mL of an aqueous solution of amoxicillin at a concentration of 40 ppm, and stirred in the dark for 20 min to allow the adsorption-desorption equilibrium between amoxicillin and the surface of the ion membrane, and then placed under visible light (λ>420 nm) for continued testing. During the test, 2 mL of the suspension was taken out every 10 min, centrifuged, and the pollutant concentration was measured at the maximum absorption wavelength of 254, 285, and 278 nm using an ultraviolet spectrophotometer, and the adsorption rate was calculated, and the adsorption rate = C / C0 (C = maximum absorbance of the reaction - minimum absorbance of the reaction; C0 = initial maximum absorbance - initial minimum absorbance). The above steps were repeated 5 times using the same photocatalytic polyetheretherketone ion exchange membrane.
[0032] Depend on Figure 1 It can be seen that the degradation rates of the photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention for the antibiotics amoxicillin, carbamazepine and norfloxacin within 1 hour are 93.54%, 88.22% and 83.42%, respectively, which proves that the photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention has a good degradation effect on antibiotics; Figure 2 It can be seen that the photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention has a reduction rate of 99.35% for heavy metal ions Cr(VI) within 10 minutes, which proves that the photocatalytic polyetheretherketone ion exchange membrane prepared by the present invention has reducing properties for heavy metal ions and has an extremely high reduction rate.
[0033] Comparative Example 1 is that CoTiO3 without Bi deposition is directly grafted with the polyetheretherketone film, Comparative Example 2 is that the Bi deposition amount is less than the Bi@CoTiO3 within the protection scope of the present invention, and Comparative Example 3 is that the Bi deposition amount is greater than the Bi@CoTiO3 within the protection scope of the present invention. The degradation rates of amoxicillin and carbamazepine in Example 1 and Comparative Examples 1-3 are as follows: Figure 3 and Figure 4 As shown by Figure 3 and Figure 4We can see that the degradation rates of amoxicillin and carbamazepine in Example 1 for 1 h reached 93.54% and 88.22%, respectively, which can effectively degrade amoxicillin and carbamazepine, while the degradation rates of amoxicillin and carbamazepine in Comparative Example 1 were only about 40%. Comparative Examples 2 and 3 were loaded with Bi, so the degradation rates were better than those in Comparative Example 1, reaching 60-70%, but still not as good as in Example 1. This proves that the more Bi is loaded, the better, and a reasonable range is required to maximize the degradation rate of antibiotics, further proving the superiority and accuracy of the present application.
[0034] Figure 5 The photocatalytic polyetheretherketone film prepared in Example 1 repeatedly degrades amoxicillin. Figure 5 We can see that the photocatalytic polyetheretherketone film prepared by the present application is repeatedly used to degrade amoxicillin. The degradation rate curves of the five cycles are almost overlapped, and the degradation rate and degradation speed have almost no change, which proves the repeatability of the photocatalytic polyetheretherketone film prepared by the present invention.
[0035] Figure 6 This is a real picture of the photocatalytic polyetheretherketone film prepared in Example 1, proving the successful preparation of the present invention.
[0036] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a photocatalytic polyetheretherketone ion exchange membrane, characterized in that: The method: S1: drying polyetheretherketone powder, mixing it with an antioxidant and a silane coupling agent, extruding it using a twin-screw extruder, cooling it, and pelletizing it to obtain polyetheretherketone pellets; S2: putting the polyetheretherketone pellets obtained in S1 into a single screw extruder, extruding and casting, and longitudinally stretching to obtain a polyetheretherketone film; S3: mixing the polyetheretherketone film obtained in S2 with sodium borohydride and pouring into a dimethyl sulfoxide solution, performing ultrasonic dispersion, and after the reaction is complete, washing and drying to obtain a polyetheretherketone film with hydroxyl groups on the surface; S4: immersing the polyetheretherketone film with hydroxyl groups on the surface obtained in S3 in an acetic acid solution of 4-aminobenzoic acid, and after the reaction is complete, washing and drying to obtain a polyetheretherketone film containing amino and carboxyl side groups; S5: mixing cobalt acetate tetrahydrate, tetrabutyl titanate, ethanol, N'N-dimethylformamide and acetic acid solution, and then adding polyvinyl pyrrolidone to complete the reaction to obtain cobalt titanate spinning gel; S6: The spinning gel obtained in S5 is loaded into a syringe with a stainless steel needle, and fibers are prepared by electrospinning, and the fibers are calcined at high temperature to obtain CoTiO3 nanofibers; S7: mixing the CoTiO3 nanofibers obtained in S6 with bismuth nitrate and ethylene glycol, and transferring the mixture into a photocatalytic reactor, and obtaining Bi@CoTiO3 after the reaction is complete; S8: mixing the polyetheretherketone film containing amino and carboxyl side groups obtained in S4, the Bi@CoTiO3 obtained in S7 and the silane coupling agent aqueous solution, heating and reacting, and obtaining a photocatalytic polyetheretherketone ion exchange membrane.
2. The method according to claim 1, characterized in that In S1, the antioxidant is 3-5% of the mass of the polyetheretherketone powder, the silane coupling agent is 3-5% of the mass of the polyetheretherketone powder, and the extrusion temperature is 370-390°C; in S2, the extrusion temperature is 350-370°C, and the thickness of the polyetheretherketone film is 0.15-0.5mm.
3. The method according to claim 1, characterized in that The mass ratio of polyetheretherketone film and sodium borohydride in S3 is 1.5~3:1, ultrasonic dispersion is 1~2h, reaction temperature is 100~160℃, and reaction time is 12~24h.
4. The method according to claim 1, characterized in that: The concentration of 4-aminobenzoic acid in S4 is 0.2~0.5g / mL, and the reaction time is 4~8h.
5. The method according to claim 1, characterized in that In S5, the ratio of cobalt acetate tetrahydrate, tetrabutyl titanate, ethanol, N'N-dimethylformamide and acetic acid is 15~50g:20~70mL:160mL:20mL:20mL, and the ratio of cobalt acetate tetrahydrate and polyvinyl pyrrolidone is 15~50g:15~50g.
6. The method according to claim 1, characterized in that The parameters of the electrospinning method in S6 are: the distance between the needle and the tin foil is 15~20cm, the spinning voltage is 15~20kV, and the spinning speed is 0.3~0.6mL / h.
7. The method according to claim 1, characterized in that In S6, the calcination temperature is 550~700℃, the heating rate is 2℃ / min, and the calcination time is 2~6h.
8. The method according to claim 1, characterized in that The ratio of CoTiO3 nanofibers, bismuth nitrate and ethylene glycol in S7 is 10g:0.38~0.76g:100mL; the concentration of the silane coupling agent aqueous solution in S8 is 3wt%, and the ratio of the polyetheretherketone film containing amino and carboxyl side groups, Bi@CoTiO3 and the silane coupling agent aqueous solution is 100g:10~30g:250mL.
9. A photocatalytic polyetheretherketone ion exchange membrane, characterized in that: The photocatalytic polyetheretherketone ion exchange membrane is prepared by any preparation method according to claims 1-8.
10. The use of the photocatalytic polyetheretherketone ion exchange membrane according to claim 9, characterized in that: The photocatalytic polyetheretherketone ion exchange membrane is used in water pollution treatment.
Citation Information
Patent Citations
Preparation method of Bi3+doped CoTiO3 nano-powder with dark catalysis capability
CN102936038A
Bismuth oxyiodide-based composite photocatalyst and preparation method thereof
CN111659425A
Anti-static polyether-ether-ketone composite film as well as preparation method and application thereof
CN119220082A
Electrospun nanofibrous polymer membrane for use in air filtration applications
US20230167591A1
Cited By
PEEK composite film as well as preparation method and application thereof
CN121797406A
PEEK composite film, preparation method and application thereof
CN121797406B